Analisis Portofolio Saham Perusahaan Perikanan di PT Bursa Efek Jakarta - Iis Diatin; Moch Prihatna Sobari; Hanen Dyawarman (Buletin Ekonomi Perikanan, 2004)
Portofolio analysis of the fisheries companies share is conducted to evaluate expected return of combination those companies share. There are four fisheries companies registered in Bursa Efek Jakarta. The four companies are PT Anugerah Tambak Perkasindo Tbk, PT Fishindo Kusuma Sejahtera Tbk. PT Darma Samudra Fishing Industries Tbk and PT Bahtera Adimina Samudera Tbk. The result show that PT Anugerah Tambak Perkasindo Tbk and PT Fishindo Kusuma Sejahtera Tbk have positive expected return and optimum share combination.